It's about Time : Couples and Careers - Moen, Phyllis (Book collections on Project MUSE., 2003)
How do two-career couples manage in a one-career world?It's about Time examines this mismatch between outdated scripts and the experiences of dual-earner couples. It broadens our understanding of occupational and family career strategies couples use in light of the widening gap between their real lives and the outdated work-hour and career-path roles, rules, and regulations they confront. It's about Time draws on the data from the Cornell Couples and Careers Study to demonstrate that:*Regardless of income, time is a scarce commodity in dual-earner households. With two jobs, two commutes, often long work hours, high job demands, business travel, several cars, children, ailing relatives, and/or pets - time is always an issue.*Time is built into jobs and career paths in ways that make continuous full-time (40 or typically more hours a week) paid work a fact of life in American society. *The multiple strands of life-career, family and personal-unfold over time. Spouses move through their life courses in tandem, with early choices - to have children or not, to work long hours or not, to switch jobs or not, to relocate for his or her career or not-all having long-term consequences for life quality and for gender inequality.The evidence from this book suggests that it is about time for the United States to confront the realities and needs of contemporary working couples and indeed, all members of the new workforce. To do so requires more than Band-Aid, short-term (and often short-sighted) policy remedies. It's about Time argues that it is essential to re-imagine and reconfigure work hours, workweeks, and occupational career paths in ways that address the widening gaps between the time needs and goals of workers and their families, at all ages and stages of the life course.